Relationship between early-onset muscle soreness and indirect muscle damage markers and their dynamics after a full marathon - Katsuyuki Tokinoya; Keisuke Ishikura; Song-Gyu Ra; Kei Ebina; Shumpei Miyakawa; Hajime Ohmori (Elsevier, 2020)
Background/Objective: Muscle soreness and damage occurs after completing a full marathon. Here we refer to muscle soreness induced by prolonged running as early-onset muscle soreness (EOMS) because muscle soreness and damage markers induced after prolonged running are different from delayed-onset muscle soreness (DOMS) and muscle damage markers induced after eccentric contraction, such as resistance exercise. The dynamics and relationship between muscle damage markers and EOMS are unclear; therefore, in this study, we aimed to elucidate the relationship between EOMS and indirect muscle damage markers, and their dynamics after a full marathon. Methods: The following measurements were performed in 19 subjects who completed a full marathon: perceived muscle soreness (using a numeric rating scale), thigh circumference (CIR), hip joint range of motion (ROM), jump height (JH) and muscle damage marker activities in the blood (CK, AST, LDH, ALD) before (Pre), after (Post) and every day for 4 days after a full marathon (D1−4). Results: EOMS was induced, as determined by the numeric rating scale score peaking immediately after a full marathon. ROM and JH significantly decreased and all muscle damage markers significantly increased after a full marathon. Serum CK and AST peaked at D1. Serum LDH and ALD peaked at Post and D3. Each marker showed different dynamics. CIR significantly decreased after a full marathon. Conclusion: Muscle soreness peaked and muscle damage markers in the blood showed different dynamics after a full marathon. In other words, this is different from DOMS.